Editors’ Introduction: Opening Conversations on Islam, Society, and Knowledge in Asian Social Science - Asep Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2019)
This inaugural issue of JASSR opens a scholarly conversation on Islam, society, and knowledge in Asian social science. Its five articles examine sharia and citizenship in Indonesia and Malaysia, repression and subjectivity in Babel, the contrasting Islamic political thought of Abdurrahman Wahid and Ayatollah Khomeini, Indonesian Muslim wedding rituals in the Netherlands, and knowledge transmission in Pesantren Miftahul Huda. Together, they show how religion, law, ritual, political authority, migration, education, and cultural texts shape social meaning across different settings. As a first edition, the issue is more than a collection of studies; it marks the journal’s commitment to grounded, comparative, and intellectually open scholarship that links local cases to wider debates in Asian social science.